Effects of High-Definition and Conventional Transcranial Direct-Current Stimulation on Motor Learning in Children - Cole, Lauran; Giuffre, Adrianna; Ciechanski, Patrick; Carlson, Helen L.; Zewdie, Ephrem; Kuo, Hsing-Ching; Kirton, Adam (Frontiers in Neuroscience, 2018)
Background: Transcranial direct current stimulation (tDCS) can improve motor learning in children. High-definition approaches (HD-tDCS) have not been examined in children. Objectives/Hypothesis: We hypothesized that primary motor cortex HD-tDCS would enhance motor learning but be inferior to tDCS in children. Methods: Twenty-four children were recruited for a randomized, sham-controlled, double-blinded interventional trial (NCT03193580, clinicaltrials.gov/ct2/show/NCT03193580) to receive 1) right hemisphere (contralateral) primary motor cortex (M1) 1mA anodal conventional 1x1 tDCS (tDCS), 2) right M1 1mA anodal 4x1 HD-tDCS (HD-tDCS), or 3) sham. Over five consecutive days, participants trained their left hand using the Purdue Pegboard Test (PPTL). The Jebsen-Taylor Test, Serial Reaction Time Task, and right hand and bimanual PPT were also tested at baseline, post-training, and 6-week retention time (RT). Results: Both the tDCS and HD-tDCS groups demonstrated enhanced motor learning compared to sham with effects maintained at six weeks. Effect sizes were moderate-to-large for tDCS and HD-tDCS groups at the end of day 4 (Cohen’s d tDCS=0.960, HD-tDCS=0.766) and day 5. (tDCS=0.655, HD-tDCS=0.851). Enhanced motor learning effects were also seen in the untrained hand. HD-tDCS was well tolerated and safe with no adverse effects. Conclusions: HD-tDCS and tDCS can enhance motor learning in children. Further exploration is indicated to advance rehabilitation therapies for children with motor disabilities such as cerebral palsy.